Insights into optimising education for patients living with diabetes mellitus: A model for the post‐pandemic era, informed by survey data - Petra Hanson; Dilan Parmar; Pranay Deo; Daniella Whyteoshodi; Charlotte Gotts; Paul J. O'Hare; Harpal Randeva; Thomas M. Barber (Wiley, 2022)
Abstract Background Patient education represents the key element in the management of diabetes mellitus (DM) and has changed dramatically during the last 3 years. Uptake of structured education is poor, and patient perception of received education varies greatly. The purpose of this study was to assess patients' perception of adequacy of delivered education, barriers to attending structured courses and preferences for ongoing DM‐related education. Methods Patients living with Type 2 DM attending diabetes clinics were invited to complete a questionnaire about their understanding of DM, adequacy of offered education and desired features of future courses, following their clinic appointment at University Hospitals Coventry and Warwickshire (UHCW). Those interested (n = 146) completed this questionnaire. Results Participants' mean age was 58.2 years (standard deviation [SD] 13.6, median 59, interquartile range [IQR] 50-66), mean body mass index 34.5 Kgm-2 (SD 9.1, median 33.7 Kgm-2, IQR 29.8-41.7) and duration of T2DM was 13 years (SD 10, median 10 years, IQR 3-19). Thirty‐one per cent of participants received no education at the time of their diagnosis with 51% of participants reporting no ongoing DM‐related education. Thirty‐seven per cent of participants did not understand the meaning of HbA1c. Preference for face‐to‐face versus remote delivery of DM‐related education was roughly split, with 51% preferring the former. Attention to self‐compassion and mental health needs were identified as key elements currently missing from DM‐related education. Conclusion The provision of DM‐related education pre‐pandemic did not meet patients' needs. Gaining insight and understanding into the gaps within current DM‐related educational provision and patient preferences for its delivery are key strategies in the development of reformed DM‐related education that will ultimately equip patients with improved self‐management skills.